Rare masterpieces of russian piano music: eleven pieces by Glinka, Blakirev, Glazunov and others - Feofanov, Dmitry. 1957- (Dover classical music for keyboard, 1984)
In this volume, University of Kentucky musicologist Dmitry Feofanov presents eleven overlooked masterpieces -important Russian piano works of the late 18th to 20th centuries virtually unobtainable elsewhere.